Increasing the level of fitness of female students with the help of sports and recreational tourism - Valeria Tyshchenko; Olga Sokolova; Halyna Omelianenko; Stanislav Ivanenko; Ivan Hlukhov; Iurii Grabovskyi; Olha Koltsova; Andrey Kuznetsov (Jan Długosz University in Częstochowa, 2022)
The aim of the research was to develop and test Physical Education program for 20- and 21--year-old female students of Zaporizhzhia National University and Kherson State University using means of sports recreational tourism to improve their fitness. The relevance of the research is experimental approbation and further practical implementation of the aforementioned PE program featuring sports recreational tourism, into the Physical Education process for higher education. The research focuses on different aspects concerning PE, sports and students health. The results of the research have shown a significant optimization of cardiovascular system fitness level of students who attended Physical Education classes with the use of sports recreational tourism and were exposed to different types of training (from technical and tactical to special physical training). The researchers evaluated the dynamics of the integral indices of the cardiovascular system among the female students of the higher educational institutions during the course of Physical Education activities taking advantage of sports recreational tourism. It was concluded that the coherence level of the cardiovascular and respiratory systems has increased. Aerobic and mixed performance increase and cardiac activity normalization that can be seen when changing to a normotonic regulation of cardiac performance were observed.